Dosimetric characteristics of LinaTech DMLC H multi leaf collimator: Monte Carlo simulation and experimental study. (6th March 2017) - Molazadeh, Mikaeil; Zeinali, Ahad; Robatjazi, Mostafa; Shirazi, Alireza; Geraily, Ghazale
Abstract: This study evaluated the basic dosimetric characteristics of a Dynamic Multi Leaf Collimator (DMLC) using a diode detector and film measurements for Intensity Modulated Radiation Therapy Quality Assurance (IMRT QA). The EGSnrc Monte Carlo (MC) simulation system was used for the determination of MLC characteristics. Radiation transmission and abutting leaf leakage relevant to the LinaTech DMLC H were measured using an EDGE detector and EBT3 film. In this study, the BEAMnrc simulation code was used for modeling. The head of Siemens PRIMUS linac (6 MV) with external DMLC H was entered into a BEAMnrc Monte Carlo model using practical dosimetry data. Leaf material density, as well as interleaf and abutting air gaps were determined according to the computed and measured dose profiles. The IMRT QA field was used to evaluate the dose distribution of the simulated DMLC H. According to measurements taken with the EDGE detector and film, the total average measured leakage was 1.60 ± 0.03% and 1.57 ± 0.05%, respectively. For these measurements, abutting leaf transmission was 54.35 ± 1.85% and 53.08 ± 2.05%, respectively. To adapt the simulated leaf dose profiles with measurements, leaf material density, interleaf and abutting air gaps were adjusted to 18 g/cm 3, 0.008 cm and 0.108 cm, respectively. Thus, the total average leakage was estimated to be about 1.59 ± 0.02%. The step‐and‐shoot IMRT was implemented and 94% agreement was achieved between the film and MC, using 3%‐3 mm gamma criteria. The results of this study showed that the dosimetric characteristics of DMLC H satisfied international standards.